(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Review of the book Formulations of the tragic in Nelson Rodrigues’ theatre, by Elen de Medeiros. The book is a result of almost a decade of research focused on the dramaturgical poetics of Nelson Rodrigues. The researcher revisits classic formulations about the Rodriguian tragedy and proposes that the author’s dramaturgical work must be read not from classical frameworks, but from what she calls a “sliding” aspect of his dramas. In specific terms, she asserts that Nelson Rodrigues’ modern tragedy absorbs and inverts classic tragic procedures and, at the same time, mixes them with resources of comedy and melodrama.